Expand 1/3(q−6) using the Distributive Property..

1 answer

To expand \( \frac{1}{3}(q - 6) \) using the Distributive Property, you multiply \( \frac{1}{3} \) by each term inside the parentheses.

Here's how it works step by step:

  1. Distribute \( \frac{1}{3} \) to \( q \): \[ \frac{1}{3} \cdot q = \frac{q}{3} \]

  2. Distribute \( \frac{1}{3} \) to \(-6\): \[ \frac{1}{3} \cdot (-6) = -\frac{6}{3} = -2 \]

Now, combine the results: \[ \frac{1}{3}(q - 6) = \frac{q}{3} - 2 \]

So, the expanded form of \( \frac{1}{3}(q - 6) \) is: \[ \frac{q}{3} - 2 \]